SPICES: A Mission Concept to Characterize Long Period Planets from Giants to Super-Earths. Issue Volume 8:Issue S293(2012) (29th April 2014) - Boccaletti, Anthony; Maire, Anne-Lise; Galicher, Raphaël; Baudoz, Pierre; Mawet, Dimitri; Trauger, John; Schneider, Jean; Traub, Wes; Stam, Daphne; Lagage, Pierre-Olivier; Gratton, Raffaele; ,
Abstract: SPICES (Spectro-Polarimetric Imaging and Characterization of Exoplanetary Systems) was proposed in 2010 for a five-year M-class mission in the context of ESA Cosmic Vision. Its purpose is to image and characterize long-period extrasolar planets located at several AUs (0.5-10 AU) from nearby stars (<25 pc) with masses ranging from a few Jupiter masses down to super-Earths (~2 Earth radii, ~10 M⊕ ), possibly habitable. In addition, circumstellar disks as faint as a few times the zodiacal light in the Solar System can be studied. SPICES is based on a 1.5-m off-axis telescope and can perform spectro-polarimetric measurements in the visible (450 - 900 nm) at a spectral resolution of about 40. This paper summarizes the top science program and the choices made to conceive the instrument. The performance is illustrated for a few emblematic cases.